2021
DOI: 10.1002/ppul.25788
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study for comparative assessment of dual‐energy computed tomography and single‐photon emission computed tomography V/Q scanning for lung perfusion evaluation in infants

Abstract: Objective: To evaluate clinical applications of dual-energy computed tomography (DECT) in pediatric-specific lung diseases and compare ventilation and perfusion findings with those from single-photon emission computed tomography (SPECT-CT) V/Q. Methods: All patients at our institution who underwent exams using both techniques within a 3-month period were included in this study. Two readers independently described findings for DECT, and two other readers independently analyzed the SPECT-CT V/Q scan data. All fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Notably, LPS is associated with a nontrivial radiation exposure (0.5-1.3 mSv) for children already at risk for radiation-associated complications due to serial catheterizations and imaging. [10][11][12][13] While CMR avoids radiation, it often requires anesthesia and can be time-consuming. Further, the accuracy of CMR estimates of Q p maldistribution can also be affected by turbulent flow at sites of discrete stenosis, or due to technical errors, such as incorrect planning of scan parameters or angles.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, LPS is associated with a nontrivial radiation exposure (0.5-1.3 mSv) for children already at risk for radiation-associated complications due to serial catheterizations and imaging. [10][11][12][13] While CMR avoids radiation, it often requires anesthesia and can be time-consuming. Further, the accuracy of CMR estimates of Q p maldistribution can also be affected by turbulent flow at sites of discrete stenosis, or due to technical errors, such as incorrect planning of scan parameters or angles.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, atelectatic lung might appear as non-perfused, and therefore the anatomical images must be viewed in concert [ 26 ]. When imaging lung that is denser, such as in atelectasis or in intrinsically dense lungs such as in neonates, older infants and those with chronic lung disease, one should use the “dense lung” tool [ 27 ]. This change results in increased maximal Hounsfield units analyzed, ultimately including perfused lung that would otherwise be missed (Fig.…”
Section: Scanner Modesmentioning
confidence: 99%
“…These exams are usually ultra-high-pitch scans, particularly if the child is not sedated. However, dual-energy CT can be used to assess blood flow to the parenchyma, which might decrease the need for additional nuclear medicine ventilation–perfusion scan [ 27 ]. The most important post-processing tool is the pulmonary blood volume.…”
Section: Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the attenuation properties of iodine, DECT provides pulmonary blood volume maps and quantifies the iodine concentration in the parenchyma, thus allowing simultaneous analysis of the gray-scale vasculature and color-scale parenchymal perfusion ( 13 ). In infants with chronic lung diseases and/or PH, DECT exhibited a similar efficacy to ventilation/perfusion scintigraphy for lung perfusion assessment ( 14 ). Moreover, it had been demonstrated that DECT is a valuable tool for diagnosing PH, regardless of the underlying mechanism or the age of the patient ( 13 , 15 ).…”
Section: Introductionmentioning
confidence: 99%